Pengaruh Penggunaan Media Video Animasi Motion Graphic terhadap Kemampuan Menulis Teks Biografi Siswa Kelas X SMA Negeri 6 Kota Bengkulu - Febriansyah, Ardo; Gumono, Gumono; Noermanzah, Noermanzah (Jurnal Korpus, 2025)
The development of technology has a significant impact on the world of education, one of which is the increasing need for relevant learning media. Motion Graphic animation video media is predicted to influence the ability to write biographical texts. Therefore, this study aims to determine the effect of using Motion Graphic animation video learning media on the ability to write biographical texts of class X students of SMA Negeri 6 Kota Bengkulu. This study uses a quantitative approach and quasi-experimental method, comparing pretest and posttest scores after using Motion Graphic animation video media. The population of this study was 214 students, with a sample of 34 students of class X MIPA C. The data collection technique used a test technique. The data analysis technique used a paired t-test. The results showed that there was an effect of Motion Graphic animation video media on the ability to write biographical texts seen from the advantages of this media such as attracting students' attention because it combines sound and images. This is evidenced by the T test, t_count is greater than t_table which is 11.666 greater than 2.03. from the sign value (2-tailed) which is 0.000 less than 0.05 then Ha is accepted. It is hoped that in the future, various technology-based learning media can be developed that are appropriate to the needs and characteristics of today's students.